1992
DOI: 10.1159/000168466
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Prognosis of Patients with Acute Renal Failure over a Period of 15 Years: An Analysis of 710 Cases in a Dialysis Center

Abstract: In order to evaluate the changes in causes and outcome of acute renal failure (ARF) during the years 1975-1989, 710 patients treated in our dialysis center were analyzed. We compared the etiology, the severity and catabolic state of ARF, the techniques of renal replacement therapy, which were employed and the ages and mortality rates of these patients, who received dialysis therapy during the years 1975-79 (n = 227), 1980-84 (n = 240) and 1985-89 (n = 243). The number of postoperative, posttraumatic and non-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 19 publications
0
12
0
3
Order By: Relevance
“…Previous studies that examined trends in ARF-associated outcomes have yielded a spectrum of conclusions, with reports of a decline (11,12,14,16,17), increase (15), and no change in in-hospital mortality (13). These studies generally have been limited by relatively small sample sizes and reliance on a single center's experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies that examined trends in ARF-associated outcomes have yielded a spectrum of conclusions, with reports of a decline (11,12,14,16,17), increase (15), and no change in in-hospital mortality (13). These studies generally have been limited by relatively small sample sizes and reliance on a single center's experience.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of 80 studies of ARF involving 15,897 patients between 1970 and 2004 concluded that mortality rates have remained unchanged (10). The handful of studies that have specifically examined mortality rates of ARF over time have been small (N Յ 710) and have yielded conflicting conclusions (11)(12)(13)(14)(15)(16)(17). Using the Nationwide Inpatient Sample (NIS), a large and nationally representative administrative database of hospital discharges from 1988 to 2002, we attempted to determine secular trends in the incidence, inhospital mortality, length of stay (LOS), and disposition (discharge to home versus posthospital care) for patients with ARF and ARF-D.…”
mentioning
confidence: 99%
“…Biesenbach et al [50] studied the prognosis of patients with ARF requiring dialysis (in recent years continuous hemofiltration) between 1975 and 1989. This report is especially relevant to the discussion of the evaluation of prognosis during the last decades.…”
Section: Prognosis For Patients With Arf 1975-1995mentioning
confidence: 99%
“…Multiple factors relate to an effect on the prognosis, but advance in blood purification technology, 13 particularly an increase in the number of patients treated by continuous hemodiafiltration, is one of the main factors underlying the improved prognosis. i4 This may be related to the fact that treatment by continuous hemodiafiltration, even in patients with acute renal failure, provides continuous transfusion of a high-calorie fluid that maintains the dynamic state of the body fluids, and maintains constancy of the acid-base balance of the blood.…”
Section: Discussionmentioning
confidence: 99%